Nordic light : modern Scandinavian architecture - Plummer, Henry, 1946- (London : Thames & Hudson, 2016)
This book celebrates established icons, newly discovered gems and contemporary masterworks that represent the highest expression of Scandinavian design and response to their environment. Fifty projects are featured in detail, ordered according to the way in which different light conditions have imparted particular qualities on the buildings. Henry Plummer treats his subject from a uniquely authoritative perspective in which his words resonate directly with his artfully taken images. Books that give a true sense of the magical light that have shaped great buildings are rare: this is a publication to savour.
Includes bibliographical references
Keywords: Architecture -- History -- 20th century -- Scandinavia; Architecture -- History -- 21st century -- Scandinavia; Daylighting; Light in architecture; Light -- Physiological effect